Studies on piezo coefficients of PLD and sol-gel grown PZT thin film for devices. Issue 193 (13th October 2018) - Natarajan, V.; Varadarajan, E.; Rath, Martando; Parui, Jayanta
Abstract: The effect of electrical (DC) contact poling processes on the ferroelectric and piezoelectric properties of sol–gel and pulsed laser-deposited PZT thin films has been investigated as a function of the poling field, temperature and time. The remnant polarization and piezoelectric coefficient are found to increase with and saturate at dc-poling field of 100- 300 kV/cm, temperature of 100–120 °C and poling time of 10–20 min. as compared with un-poled PZT thin films. The P-E hysteresis loops of poled PLD grown PZT films shows sharper switching behaviour as compared to imbalanced loop in sol-gel grown films. An improvement of piezoelectric and ferroelectric properties of sol–gel PZT thin films is found, as compared to those deposited using pulsed laser deposition (PLD), indicating that a poling process is required for sol–gel PZT thin films.